Management of Large-Vessel Vasculitis With FDG-PET. Issue 14 (April 2015) - Soussan, Michael; Nicolas, Patrick; Schramm, Catherine; Katsahian, Sandrine; Pop, Gabriel; Fain, Olivier; Mekinian, Arsene; Roever., Leonardo
<x xml:space="preserve">Abstract</x> Abstract We aimed to clarify the role of 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) in the management of large-vessel vasculitis (LVV), focusing on 3 issues which are as follows: describe and determine the different FDG-PET criteria for the diagnosis of vascular inflammation, the performance of FDG-PET for the diagnosis of large-vessel inflammation in giant cell arteritis (GCA) patients, and the performance of FDG-PET to evaluate the disease inflammatory activity in Takayasu arteritis (TA) patients. MEDLINE, Cochrane Library, and EMBASE database were searched for articles that evaluated the value of FDG-PET in LVV, from January 2000 to December 2013. Inclusion criteria were American College of Rheumatology criteria for GCA or TA, definition PET positivity threshold, and >4 cases included. Sensitivity (Se) and specificity (Sp) of FDG-PET for the diagnosis of large-vessel inflammation were calculated from each included individual study, and then pooled for meta-analysis with a random-effects model. Twenty-one studies (413 patients, 299 controls) were included in the systematic review. FDG-PET showed FDG vascular uptake in 70% (288/413) of patients and 7% (22/299) of controls. Only vascular uptake equal to or higher than the liver uptake was significantly different between GCA/TA patients and controls (P < 0.001). The meta-analysis of GCA patients (4 studies, 57 patients) shows that FDG-PET has high Se and Sp for the diagnosis of large-vessel inflammation in GCA patients in comparison to controls, with a pooled Se at 90% (95% confidence interval [CI], 79%–93%) and a pooled Sp at 98% (95% CI, 94%–99%). The meta-analysis of TA patients (7 studies, 191 patients) shows that FDG-PET has a pooled Se at 87% (95% CI, 78%–93%) and Sp at 73% (95% CI, 63%–81%) for the assessment of disease activity in TA, with up to 84% Sp, with studies using National Institutes of Health criteria as the disease activity assessment scale. FDG-PET showed good performances in the diagnosis of large-vessel inflammation, with higher accuracy in GCA patients than in TA patients. Although a vascular uptake equal to or higher than the liver uptake appears to be a good criterion for the diagnosis of vascular inflammation, further studies are needed to define the threshold of significance as well as the clinical significance of the vascular uptake.